WORKING WITH COMMUNITIES IN ASSET MAPPING USING ABCD APPROACH IN ALAUDDIN STATE ISLAMIC UNIVERSITY MAKASSAR - Nur, Serliah (Journal of Islam and Science, 2014)
Asset Based Community Development (ABCD) approach has gained popularity as one methodology used in Community-Driven Development (CDD) in approaching the desired change in our left behind local community in Indonesia generally and South Sulawesi specifically. UIN Alauddin as a higher education institution has one responsibility among the three assignments not only to teach and to do research but also to serve the community. In strengthening this function, UIN plans to implement more persistently students and teaching staffs community service with the ABCD approach. This paper discusses the ABCD approach and how it had been implemented for the above purpose. We evaluate how the assigned working group (pokja) from UIN had tried to implement this in Selayar Island and a student community service using this ABCD approach in the specific field of community health in Bantaeng. Finally we list the opportunities and challenges from the discussion to propose a better recommendation for future implementation of this ABCD for the local context in South Sulawesi.